2019
DOI: 10.1371/journal.pone.0220100
|View full text |Cite
|
Sign up to set email alerts
|

The difference in hemodynamic responses between dominant and non-dominant hands during muscle contraction and relaxation: An fNIRS study

Abstract: The present study used functional near-infrared spectroscopy (fNIRS), and investigated the differences in neural activation of ipsi- or contralateral hemispheres between right dominant and left non-dominant hands among right-handed subjects using consecutive motor tasks with muscle contraction and relaxation. The subjects performed tasks under four conditions: (1) right hand up (R-Up), (2) left hand up (L-Up), (3) right hand down (R-Down), and (4) left hand down (L-Down). The peak amplitude of oxy-Hb was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In the current study, three left-handed participants, i.e., participants 5, 17, and 18, were asked to perform motor imagery with their non-dominant hand. Given the established hemispheric asymmetry related to handedness (Maruff et al, 1999;Lee et al, 2019;Yokoyama et al, 2019), it is plausible that left hand imagery combined with right hemisphere fNIRS recordings would have resulted in heightened BCI decoding accuracies for these three participants. When excluding these three participants from our univariate analyses, single-trial accuracies rose to 58.44% (HbO) and 58.00% (HbR), previously 56.85 and 54.81%.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In the current study, three left-handed participants, i.e., participants 5, 17, and 18, were asked to perform motor imagery with their non-dominant hand. Given the established hemispheric asymmetry related to handedness (Maruff et al, 1999;Lee et al, 2019;Yokoyama et al, 2019), it is plausible that left hand imagery combined with right hemisphere fNIRS recordings would have resulted in heightened BCI decoding accuracies for these three participants. When excluding these three participants from our univariate analyses, single-trial accuracies rose to 58.44% (HbO) and 58.00% (HbR), previously 56.85 and 54.81%.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…These findings provide evidence for further exploration of the interaction 1 Introduction Human execute motor tasks and promote individuals to complete activities of daily life and social interaction (Shumway-Cook and Woollacott, 2014). The completion of motor tasks consists of corresponding muscle contractions and stretches, so it is important to generate accurate motor control, which is considered to be the fundamental factor of movement (Yokoyama et al, 2019). Previous studies, such as electroencephalography (EEG) and functional magnetic resonance imaging (fMRI), have found that upper limb movement is regulated by corresponding regions of the cerebral cortex (Long et al, 2016;Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a review article from Hammond, the author also concluded the similar findings of the correlates of the handedness in primary motor cortex ( Hammond, 2002 ). In addition, a fNIRS study from Yokoyama et al showed that non-dominant side had greater variability in adjustment time than the dominant side under the same muscle relaxation and contraction conditions ( Yokoyama et al, 2019 ). These findings suggest that there are significant differences in motor control between the dominant and non-dominant sides of healthy adults, and motor control might be more difficult on the non-dominant side.…”
Section: Discussionmentioning
confidence: 99%
“…2A). The NIRS probes were attached based on the international 10-20 electrode system employed in electroencephalography (EEG), and the Cz position (vertex reference) was utilized as a marker to ensure a replicable placement of the optodes 21,27) . In this study, source 7 was 2B).…”
Section: Nirs Measurementmentioning
confidence: 99%
“…In this study, source 7 was 2B). The probe position and ROI were set by following previous studies investigating motor-related cortical regions 23,27,28) . The C3 and C4 positions, based on the international 10-20 electrode system, were anatomically placed over the left and right M1 as motor hot spots, respectively, which are often used by studies involving transcranial magnetic stimulation (TMS) 29) .…”
Section: Nirs Measurementmentioning
confidence: 99%